The Effects of Metoclopramide Premedication on the Neuromuscular Blockade of Vecuronium and Mivacurium - KEŞKÜŞ, Hüsamettin; SALİHOĞLU, Ziya (Cerrahpaşa Medical Journal, 2014)
Elimination of metoclopramide is mostly made by cholinesterase enzyme. Especially cholinesterase enzyme took place at the cessation of the effects of depolarisating neuromuscular blocking agents. Cholinesterase enzyme levels can differentiate with metoclopramide administration. In this study we compared the effect of metoclopramide premedication with vecuronium and mivacurium's neuromuscular effects. Eighty patients undergoing elective general surgery operations were enrolled to the study. The patients were grouped according to the premedication of metoclopramide and to the neuromusculary blocking agent used as Group Metoclopramide-Mivacurium (n = 20), Group Mivacurium (n = 20), Group Metoclopramide-Vecuronium (n = 20), and Group Vecuronium (n = 20). The neuromuscular blockage was measured by accelomyography (TOF Guard), time to maximum blockage (sn), T25 (min.), T75 (min.), and recovery index (T25-T75) (min.) was enrolled. Student's t test, chi-square, repeated measures of ANOVA, posthoc Tukey-Kramer tests were used for statistical analysis. P < 0.05 values were accepted as statistically significant. There were no significant difference in on all data we studied. We suggest that neuromusculary functions of the patients medicated by metoclopramide and neuromusculary blocking agents should be monitorized during general anesthesia.